Acute abdomen due to ovarian congestion caused by coiling of the fallopian tube accompanied by paratubal cyst around the utero-ovarian ligament - Kim, Juyoung; Park, Daehyun; Han, Won Bo; Jeong, Hyangjin; Park, Youngse (Obstetrics & gynecology science, 2014)
Torsion of uterine adnexa is an important cause of acute abdominal pain in females. The main organ which can cause torsion is the ovaries, but torsions of the fallopian tube, subserosal myoma, paratubal cyst, and even the uterine body have been reported. The incidence of isolated fallopian tubal torsion is very rare. Even more rarely, it can coil around nearby organs such as the utero-ovarian ligament, showing similar clinical manifestations with those of adnexal torsion. We experienced an extremely rare case of acute abdomen induced by ovarian congestion triggered by the fallopian tube accompanying a paratubal cyst coiling around the utero-ovarian ligament. The right paratubal cyst was misinterpreted as being part of a cystic component of the left ovary on preoperative sonographic examination, and the coiling of the right fallopian tube accompanying the paratubal cyst was misdiagnosed as torsion of the right ovary. We report this rare case with a brief literature review.